Nursing consultation to deaf people: a contextual analysis - Araújo, Camila Crisse Justino de; Coura, Alexsandro Silva; França, Inacia Sátiro Xavier de; Araújo, Andressa Kaline Ferreira; Medeiros, Kaio Keomma Aires Silva (ABCS Health Sciences, 2015)
This study aimed at critically analyzing the contextual factors that influence Nursing consultation to deaf people. It is a critical review of literature, developed from July to August 2013, on SciELO, LILACS and IBECS databases as well as on Google Scholar and electronic portals of the Ministry of Health, of the World Health Organization and of Instituto Brasileiro de Geografia e Estatística – IBGE. Then, we proceeded to the analysis of the material collected using the Contextual Analysis method. Given the corpus of selected publications, investigated subjects were grouped into interactive layers of context, comprising: peculiarities of Nursing consultation to deaf people; obstacles faced in Nursing consultation to deaf people; sociocultural and psychological understanding of the nurse/deaf patient/intermediator; and law applied – bases for ethics practice in Nursing consultations to deaf people. It was concluded that Nursing consultation to deaf patients does not occur satisfactorily due mainly to the inadequacy of nurses, without the correct preparation in the academic area, overlooking the care to this important segment of the population.